1999
DOI: 10.1677/joe.0.1600333
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in LH secretion by male pituitaries in vitro: from the infantile to adult period

Abstract: The secretion of LH from the anterior pituitary of male rats was studied at different periods of postnatal development. According to an established classification we used rats 14 (infantile), 23 (juvenile), 45 (pubertal) and 90 (adult) days old. By using an in vitro incubation system, both basal and stimulated LH secretion were studied in the same gland. Age-related differences were observed in basal LH secretion, with juvenile and pubertal pituitaries showing higher secretion compared with infantile and adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The albino rat was chosen as an animal model, as data from rats on aspartame closely resemble human data [26]. The ages studied ranged from 3 months (age of administration) to 9 months (age of sacrifice) according to the established classification of Bello-Pineda et al [27]. Adult age was chosen as the main period of reproductive concern.…”
Section: Discussionmentioning
confidence: 99%
“…The albino rat was chosen as an animal model, as data from rats on aspartame closely resemble human data [26]. The ages studied ranged from 3 months (age of administration) to 9 months (age of sacrifice) according to the established classification of Bello-Pineda et al [27]. Adult age was chosen as the main period of reproductive concern.…”
Section: Discussionmentioning
confidence: 99%
“…Pituitary cell cultures from PN5 and PN15 male rats responded to GnRH-stimulation with a 6-and 14-fold increase in LH secretion, respectively, whereas E19 fetal cultures failed to respond to GnRH. Although the mechanisms for these developmental changes are unclear, pituitary cell cultures from infant rats are known to be more responsive to GnRH stimulation than are adult pituitary cultures (35)(36)(37), and others have been unable to detect LH in the culture medium when fetal pituitary cells are stimulated by GnRH (38). Low levels of GnRH-R mRNA in the fetal pituitary may explain the absence of a GnRH effect (2).…”
Section: Discussionmentioning
confidence: 99%
“…At postnatal stages, infantile and adult, we observed that type I/III collagen persisted as inducer of dispersed pituitary cell migration. During the infantile period this response has been correlated with the intense pituitary cell re-accommodation observed (Yashiro et al, 1981;Soji et al, 1994;Bello-Pineda et al, 1999). In the adult period, although male pituitary gland cytoarchitecture is relatively stable, cell movements have to be present for cell renewal (Takahashi et al, 1984;Carbajo-Pérez and Watanabe, 1990).…”
Section: Discussionmentioning
confidence: 97%
“…An increase in number and distribution throughout the gland of folliculo-stellate cells are observed with age, reaching a plateau at 40 days of age (Soji et al, 1994). In addition, LH-positive cells in adult pituitary cells are located near the periphery and at the anterior-ventral area of the gland (Nakane, 1968(Nakane, , 1970Bello-Pineda et al, 1999), but infantile glands showed that these cells are localized mainly along the anterior face of the gland, forming a band (Bello-Pineda et al, 1999). According to this, during the first weeks after birth, pituitary cells have to re-arrange in order to obtain the cytoarchitecture present in the adult gland.…”
Section: Introductionmentioning
confidence: 99%